2016
DOI: 10.3892/ol.2016.4668
|View full text |Cite
|
Sign up to set email alerts
|

Shift in prevalence of HPV types in cervical cytology specimens in the era of HPV vaccination

Abstract: Abstract. The aim of the present population-based cohort study was to analyze the association between the prevalence of 32 types of human papilloma virus (HPV) in 615 female patients with abnormal cervical cytopathology findings. In total, 32 HPV types were screened by DNA array technology. HPV infection was detected in 470 women (76.42%), 419 of whom (89.15%) were infected with ≥1 high-risk (HR)-HPV type. HPV16, which is recognized as the main HR-HPV type responsible for the development of cervical cancer, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 47 publications
3
25
0
Order By: Relevance
“…In our study, there was no statistically significant linear correlation between the HPV(C) status detected by specific PCR amplification of HPV DNA and the presence of Pap-detected koilocytes (P > 0.05). These results are in accordance with a growing body of evidence that in many cases there is no full correspondence between cytological and DNA-based test results [6,7]. For example, Richardson et al [14] recently reported a reduction in the diagnostic accuracy of Pap cytology when evaluating patients' cervical HPV status, possibly due to a heightened awareness of potential abnormalities, which led to more false-positive results.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…In our study, there was no statistically significant linear correlation between the HPV(C) status detected by specific PCR amplification of HPV DNA and the presence of Pap-detected koilocytes (P > 0.05). These results are in accordance with a growing body of evidence that in many cases there is no full correspondence between cytological and DNA-based test results [6,7]. For example, Richardson et al [14] recently reported a reduction in the diagnostic accuracy of Pap cytology when evaluating patients' cervical HPV status, possibly due to a heightened awareness of potential abnormalities, which led to more false-positive results.…”
Section: Resultssupporting
confidence: 83%
“…The cytological sign that, since the mid-1970s, has been generally considered indicative of an HPV infection is the presence of koilocytes in cervical smears [2,[3][4][5]. However, with the ever-developing advancements in molecular diagnostic tools, it has become evident that cytological and histological features of koilocytosis, or koilocytotic atypia, are not sensitive enough as indicators of the presence of HPV DNA [6,7]. Cytological or histological signs of HPV infection are, in fact, not detected in a majority of women who are positive for HPV DNA [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viral capsid L1‐protein VLPs in vaccines promote production of antibodies which might partially cross‐target similar epitopes on non‐vaccine types . Reductions in incidence have been reported for alpha 9‐species HPV31, HPV33 (related to HPV16), alpha 7‐species HPV45 (related to HPV18) and alpha 5‐species HPV51 . HPV67 might be affected similarly to HPV31.…”
Section: Discussionmentioning
confidence: 99%
“…A significant reduction in the PPV of cytology for the detection of CIN2+ was also observed, while the NPV of negative or low‐grade cytology for CIN2+ increased significantly. Results from a study on German women demonstrated decreased incidence in HPV16 and −18, as well as HPV‐31 among patients younger than 23 years of age with a shift in the distribution of non‐vaccine HPV types such as HPV‐51, −53, −56, and −66, in spite of vaccination rates around 37.5% . Their findings suggest cross‐protection for some HPV types not included in the vaccines such as demonstrated for HPV‐31.…”
Section: Introductionmentioning
confidence: 96%